Passive immunotherapy for N-truncated tau ameliorates the cognitive deficits in two mouse Alzheimer's disease models. Issue 1 (6th April 2020) - Corsetti, Veronica; Borreca, Antonella; Latina, Valentina; Giacovazzo, Giacomo; Pignataro, Annabella; Krashia, Paraskevi; Natale, Francesca; Cocco, Sara; Rinaudo, Marco; Malerba, Francesca; Florio, Rita; Ciarapica, Roberta; et al.
Abstract: Clinical and neuropathological studies have shown that tau pathology better correlates with the severity of dementia than amyloid plaque burden, making tau an attractive target for the cure of Alzheimer's disease. We have explored whether passive immunization with the 12A12 monoclonal antibody (26–36aa of tau protein) could improve the Alzheimer's disease phenotype of two well-established mouse models, Tg2576 and 3xTg mice. 12A12 is a cleavage-specific monoclonal antibody which selectively binds the pathologically relevant neurotoxic NH2 26-230 fragment (i.e. NH2 htau) of tau protein without cross-reacting with its full-length physiological form(s). We found out that intravenous administration of 12A12 monoclonal antibody into symptomatic (6 months old) animals: (i) reaches the hippocampus in its biologically active (antigen-binding competent) form and successfully neutralizes its target; (ii) reduces both pathological tau and amyloid precursor protein/amyloidβ metabolisms involved in early disease-associated synaptic deterioration; (iii) improves episodic-like type of learning/memory skills in hippocampal-based novel object recognition and object place recognition behavioural tasks; (iv) restores the specific up-regulation of the activity-regulated cytoskeleton-associated protein involved in consolidation of experience-dependent synaptic plasticity; (v) relieves the loss of dendritic spine connectivity in pyramidal hippocampal CA1 neurons; (vi) rescues the Alzheimer's disease-related electrophysiological deficits in hippocampal long-term potentiation at the CA3-CA1 synapses; and (vii) mitigates the neuroinflammatory response (reactive gliosis). These findings indicate that the 20–22 kDa NH2 -terminal tau fragment is crucial target for Alzheimer's disease therapy and prospect immunotherapy with 12A12 monoclonal antibody as safe (normal tau-preserving), beneficial approach in contrasting the early Amyloidβ-dependent and independent neuropathological and cognitive alterations in affected subjects. Abstract : Intercepting the pathologically relevant species without interfering with the physiological form(s) of protein is one of the challenges of tau-directed immunotherapy. The present study shows that antibody-mediated selective neutralization of the toxic N-truncated tau fragment in hippocampi from two transgenic Alzheimer's disease mice significantly improves the synaptic functions. Graphical Abstract: